Pengaruh Dosis Amelioran dan Umur Panen terhadap Hasil Benih G1 Kentang (Solanum tuberosum L.) Varietas Medians - Yuliany Puspitasari; Linlin Parlinah; R. Budiasih; Noertjahyani Noertjahyani (Paspalum: Jurnal Ilmiah Pertanian, 2022)
The purpose of this study was to study the effect of amelioran dose and harvest age on the yield of G1 potato varieties of Medians. This research was conducted in the experimental garden of the Faculty of Agriculture, University of Winaya Mukti, on Inceptisol soil with an altitude of 850 meters above sea level. The experiment was carried out from February to June 2021. The experimental design used was a Randomized Block Design consisting of nine combinations of amelioran treatments and harvest age, namely A (Amelioran 0 tons ha-1 + harvest age 90 days), B (Amelioran 0 tons ha-1 + harvest age 100 days), C (Amelioran 0 tons ha-1 + harvest age 110 days), D (Amelioran 10 tons ha-1 + harvest age 90 days), E (Amelioran 10 tons ha-1 + harvest age 100 days), F (Amelioran 10 tons ha-1 + harvest age 110 days), G (Amelioran 20 tons ha-1 + harvest age 90 days), H (Amelioran 20 tons ha-1 + harvest age 100 days), and I (Amelioran 20 tons ha-1 + harvest age 110 days) each treatment was repeated three times. The results of the experiment showed that the ameliorant dose and harvest age had an effect on the number of tubers, the weight of the tubers planted, and the G1 potato seed class. Dosage of ameliorant 10-20 tons ha-1 and harvest age of 90-110 days gave better yields of potato G1 seeds.